Neuromodulators for Atypical Facial Pain and Neuralgias: A Systematic Review and Meta‐Analysis. (10th October 2020) - Do, Triet M.; Unis, Graham D.; Kattar, Nrusheel; Ananth, Ashwin; McCoul, Edward D.
Abstract : Objective: To evaluate the effectiveness of neuromodulating agents for the management of atypical facial pain and primary facial neuralgias. Methods: We searched MEDLINE, Embase, CINAHL, and ClinicalTrials.gov databases for original research articles that examine the effectiveness and adverse reactions of pharmacologic therapy for the treatment of trigeminal neuralgia and atypical facial pain. Studies that included surgical interventions for atypical facial pain or facial pain secondary to other causes were excluded. Meta‐analysis was conducted for reductions in symptom scores and adverse effects. Results: Of 3, 409 articles screened, 73 full‐text articles were included, consisting of 45 observational studies and 29 randomized controlled trials. Twenty‐four different pharmacological agents were assessed; carbamazepine was the most frequently studied while botulinum toxin A demonstrated the highest consistency in reduction of symptom scores. Pooled estimate of three randomized controlled trials revealed that patients with trigeminal neuralgia who received botulinum toxin A had higher odds (odds ratio 7.46; 95% CI 3.53–15.78) of achieving a ≥50% reduction in visual analogue scale scores compared to controls. Pooled estimate of 15 observational studies showed that three‐fourths of patients with trigeminal neuralgia who received carbamazepine experienced clinically significant pain reduction (prevalence proportion 0.75; 95% CI 0.66–0.83). Conclusions: Patients receiving botulinum toxin A for trigeminal neuralgia had higher odds of achieving ≥50% reduction in pain scores. A significant proportion of patients with trigeminal neuralgia experienced positive response to carbamazepine. There was moderate evidence for amitriptyline in patients with atypical facial pain. Standardization of outcome reporting would facilitate future quantitative comparisons of therapeutic effectiveness. Laryngoscope, 131:1235–1253, 2021